GRAND PURI WATER PARK ON THE MOVE : INOVASI HOSPITALITAS KARYAWAN GPWP YOGYAKARTA - , FEBRIANA R.K ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Tourism is an important aspect of economy growth in Indonesia.To be developed, tourism needs support from all the elements of tourism industry executantsand the society to create comfortable and friendly atmosphere for the tourist. The atmosphere will be created if the people in Indonesia apply hospitalitas concept in their life. As a tourism object, Grand Puri Water Park realizes that hospitalitas role is the main capital of their product. Hospitalitas is done to create comfortable environment for the visitors who enjoy tourism attraction in that place. As a result, it is important to keep the quality of their service to get positive response from the visitors. Evaluation is needed in certain time to make innovations of service to increase the service quality of the company. Based on that concept, the writer hopes the staffs in Grand Puri Water Park understand how hospitalitas is important. Another aim from this writing is to make innovation of hospitalitas for the staffs and observe the change of the hospitalitas which is done by the staffs in that place after the innovation. Besides that, the writer uses qualitative data method which is collected from the result of direct observation, interview, participant observation, and library research to support the result of the research in Grand Puri Water Park. In order to create hospitalitas innovation of the staffs, there are some methods used which are approaching, practicing the project, and training. The writer found some obstacles in the process which are the lack of awareness of the staffs about the important of hospitalitas, domicile and age of the staffs, and the lack of the innovation from Grand Puri Water Park management itself. The service which is served by the staffs of Grand Puri Water Park is oriented to maximize satisfaction of the visitors and minimize the complain from the visitors. All of those aspects must be kept to create and boost the professional quality of the company.